Pandemics — What Can be Done Better (Economically) in the Future? - ZG Überblick (Wirtschaftsdienst)
Abstract The COVID-19 pandemic has highlighted the fragility of the health system, society and economy when global crises occur. In order to be better prepared for the next crisis, health policy, economic, legal, ethical and political questions must be answered. The Berlin-Brandenburg Academy of Sciences and Humanities (BBAW) organised a symposium on this topic on 29 June 2021. Are there better strategies for more resilience, effectiveness and justice? What can be left to the market, and what is a matter for the state? How should funding, responsibilities and decisionmaking rights be sorted within a country and across (European) national borders? Selected contributions to the symposium are summarised in this Wirtschaftsdienst-Zeitgespräch.